Effectiveness guidance document (EGD) for acupuncture research - a consensus document for conducting trials - Witt Claudia M; Aickin Mikel; Baca Trini; Cherkin Dan; Haan Mary N; Hammerschlag Richard; Hao Jason; Kaplan George A; Lao Lixing; McKay Terri; Pierce Beverly; Riley David; et al. (BMC Complementary and Alternative Medicine, 2012)
Abstract Background There is a need for more Comparative Effectiveness Research (CER) to strengthen the evidence base for clinical and policy decision-making. Effectiveness Guidance Documents (EGD) are targeted to clinical researchers. The aim of this EGD is to provide specific recommendations for the design of prospective acupuncture studies to support optimal use of resources for generating evidence that will inform stakeholder decision-making. Methods Document development based on multiple systematic consensus procedures (written Delphi rounds, interactive consensus workshop, international expert review). To balance aspects of internal and external validity, multiple stakeholders including patients, clinicians and payers were involved. Results Recommendations focused mainly on randomized studies and were developed for the following areas: overall research strategy, treatment protocol, expertise and setting, outcomes, study design and statistical analyses, economic evaluation, and publication. Conclusion The present EGD, based on an international consensus developed with multiple stakeholder involvement, provides the first systematic methodological guidance for future CER on acupuncture.